Fault Attack of SMS4 Based on Internal Collisions. Issue 7 (April 2020) - Zhu, Renjie; Ou, Qingyu; Luo, Fang
Abstract: A fault attack of SMS4 based on internal collision is proposed. The method assumes that the attacker can attack under the condition of selecting plaintext, and adopts the byte-oriented random fault model to successfully recover the original key by injecting the fault in the first few rounds of the encryption algorithm of the SMS4. Theoretical analysis and experimental results show that the 60 fault injections can successfully recover the original key of the SMS4, with a probability of over 99%. If the attacker can control the location of fault injection, then only 16 fault injections are needed to successfully recover the original key of the SMS4. In general, 30 to 40 fault injections can successfully restore the original key.